WORD FORMATION OF OCCASIONAL WORDS - O.Y. TUXTASINOVA (International Journal of Literature and Language Studies, 2026)
This article provides information on the formation of occasionalisms, the characteristics of noun- and adjective-forming affixes that actively participate in occasional word formation, and the semantic aspects of occasional words formed through these affixes.